ROBERT JACKSON’S THEORY IMPLEMENTATION EFFORTS TO BUILD STUDENTS’ RELIGIOUS TOLERANCE ATTITUDE AT SMK MAHADHIKA 4 JAKARTA - Lilik Murni Mustamiah; Yayah Nurmaliyah; Desmaliza Desmaliza (Penamas, 2022)
This study aims to determine the role of religious education teachers in schools as an effort to build students' religious tolerance, supporting and inhibiting factors in an effort to build religious tolerance attitudes students, and to find out the implementation of religious education in plurality based on Robert Jackson's theory at SMK Mahadhika 4 Jakarta. This research is a qualitative research where the researcher will act as a research tool and attempt to collect data, describe and analyze data in the field through observation, interviews and documentation. The results of this study state that the role of religious teachers in building students' religious tolerance is first, through the learning process (good habits and examples). Second, the teacher participates in assisting in religious activities/social activities, both intracurricular and extracurricular. The supporting factor in building students' religious tolerance is through intracurricular and extracurricular activities. Inhibiting factors include lack of student response and self-motivation, students from incomplete families, and lack of student understanding of tolerance material. Mahadhika 4 Vocational School has implemented religious education in plurality based on Robert Jackson's theory, namely using an interpretive approach and a dialogical approach